University Masterplan and Negotiated Idealism:On the Evolution of the Masterplan of Yonsei University throughout 20th-century Korea. Issue 3 (1st September 2018) - Paek, Seunghan; An, Dai Whan
Abstract : This article explores how idealized architectural plans are negotiated in relation to the practical concerns and socio-cultural conditions of modern and contemporary Korea. As a case study, it focuses on analyzing the masterplans of Yonsei University, one of the key universities that illustrate the architectural modernity of Korea, as well as reflecting the continual interactions between different agents of power within and outside the country. Particular attention is given to the evolution of the university′s masterplans at four different points in time: the plans proposed in 1917, 1925, 1957, and 1970 respectively, all of which are compared to the 2016 map. The 1917 plan is a product made by an American architect—Henry K. Murphy—who proposed a design without visiting the site. Such a process lacking tactile engagement resulted in generating an overly western-style and also an ′ideal′ plan that does not adequately respond to actual site conditions. While the 1925 and 1957 plans are updated versions that are based on Murphy′s site visits, they still seem idealized to a great degree. It is rather the last two maps—1970 and 2016 plans—where one can detect how they manifest themselves for the changing conditions of modern and contemporary Korea; a number of those working at the university participated in the design process, which focused on generating more realistic strategies in response to South Korea′s ′compressed modernity′. Our in-depth visual analysis of the Yonsei masterplans shows how idealized plans are negotiated and reworked, thereby reflecting realistic demands for university life in material ways.